Linguistic patterns and frames in the context of the concept “wall in minds” (Altre Modernità, 2021)
For more than 30 years, the inner-German border as a physical borderbetween the GDR and FRG no longer existed. From a linguistic perspective, unificationcan be assumed. The linguistic differences between the former East and West Germansare smaller than those between the different German dialect speakers. However,categories such as Ossi, East German or Wessi, West German can still be found today,although the terms for the inhabitants of the GDR (Ossi, Ostdeutsch, Ostler etc.) aremore productive. The physical inner-German border seems to turn into a wall inpeople's minds. This article takes up the current discourse and asks about theunderlying patterns and frames that constitute this mental border or enable itsreconstruction. Autobiographical narrative interviews with people of two age groupswho grew up or were socialised at the former inner-German border serve as a basis.
Keywords: wall in minds, border, frame semantics, corpus analysis